Moving towards an education which develops competencies in the classroom-a current challenge - Pineros, V.; Moreno-Mediavilla, Daniel; Pascual López, Virginia; Palacios Ortega, Alicia (Edulearn17:8TH international conference on education and new learning technologies, 2020)
The term "competence" is already known in a business context and it is associated with the concept of quality. In regards to education, it has been used since 1992 and has been widely accepted in this field. Unfortunately, when it comes to teaching in a classroom context putting this into practice has created some confusion. Still, its polysemantic assumption has caused evaluations of students to render faulty results. The report given by PISA in 2012 referring to Colombia shows the analysis of the performance of 510.000 high school students (age 15), in Mathematics. Languages and Science from 65 countries, among which Colombia got, 376, 403, and 399, respectively, contrary to the results in 2009. This year Colombia got the best scores. In 2013, It held the last position in resolving concrete problems. In reference to the National Test (Icfes), most of the public institutions did not exceed the average in competencies and Science had the lowest score. This research paper aims to decide if the teaching of competencies and their practices are truly being developed by teachers, and the academic processes to evaluate the scientific competencies are according to the criteria stablished by PISA and ICFES. Through the application of theoretical research we can determine the development of competencies and aptitudes with regards to learning science in classrooms. Also, by analyzing them we can see how teachers apply the concepts and how high school students are evaluated in state schools in Barranquilla. This proposal aims to create a diagnosis regarding "scientific competence" as a concept, the analysis of strategies used in class to develop it, and then to formulate a workshop to develop the scientific competences properly in our public schools. A theoretical revision of the concept is necessary due to its prevalence at schools. There are some misunderstandings, some discrepancies between the concept and its practice. It is important to understand the role of the question, working in team, and problem-based class. Once it is revised, the diagnosis be consolidated in Barranquilla state schools, and a model of a class will be designed and put into practice. The main purpose would be to develop scientific competences in Science classes. At this very moment the last part of the research is being conducted, and it will be shared with the Congress.
Keywords: development of skills; scientific skill; assessment; classroom; WOS(2)